2011
DOI: 10.3109/00016489.2011.616912
|View full text |Cite
|
Sign up to set email alerts
|

15-year efficacy of uvulopalatopharyngoplasty based on objective and subjective data

Abstract: Conclusions:This follow-up showed a stable and significant decrease in median oxygen desaturation index 4% (ODI 4 ) values over the years. Approximately two thirds of the patients fulfilled the success criteria (ODI 4 reduction of 50% and < 20) after 15 years. A majority had improved/cured excessive daytime sleepiness (EDS) and was satisfied. No increased mortality rate was seen. Objectives:To evaluate sleep apnoea recordings and symptoms in patients with obstructive sleep apnoea syndrome 15 years after uvulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
3
18
1
5
Order By: Relevance
“…21 Furthermore, in our 15-year follow-up of another study of 50 OSAS patients, the median ESS score after UPPP was 6. 22 These findings are also similar to those in other studies investigating the effects of UPPP; for example, the one by Yaremchuk et al 23 and the multicenter study by Weaver et al 24 The fact that this RCT (level 1 evidence) found similar outcomes suggests that the results from previous case series are reasonably accurate, because this RCT validates the results of these previous case series studies. Our results regarding the effect of UPPP are also similar to those in another RCT, which compared therapeutic CPAP with subtherapeutic CPAP in OSAS patients.…”
Section: Discussionsupporting
confidence: 88%
“…21 Furthermore, in our 15-year follow-up of another study of 50 OSAS patients, the median ESS score after UPPP was 6. 22 These findings are also similar to those in other studies investigating the effects of UPPP; for example, the one by Yaremchuk et al 23 and the multicenter study by Weaver et al 24 The fact that this RCT (level 1 evidence) found similar outcomes suggests that the results from previous case series are reasonably accurate, because this RCT validates the results of these previous case series studies. Our results regarding the effect of UPPP are also similar to those in another RCT, which compared therapeutic CPAP with subtherapeutic CPAP in OSAS patients.…”
Section: Discussionsupporting
confidence: 88%
“…[10][11][12] All subjects, with 1 exception, were downstaged to mild residual OSA, allowing for the clinical cessation of nocturnal CPAP. The improvement in the RDI may lead to reduced long-term sequelae and may provide for increased adherence with CPAP for the subjects requiring intervention for residual disease.…”
Section: Resultsmentioning
confidence: 99%
“…The mean reduction of AHI was stable over time, 55% after 6 months and 54% after 24 months, which is higher than the mean AHI reduction of 33% in the meta‐analysis of 15 UPPP studies from 2010 . The corresponding values for ODI values in the present study were 63% and 58%, which are comparable with the results from a previous study of 158 patients from our group, with a mean reduction in ODI of 60% 1 year after UPPP, and of 52% at a 15‐year follow‐up of another cohort . Thus, the results from three different patient cohorts undergoing UPPP at our department may be considered modest but consistent and long‐lasting.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Janson et al, 48% of the 34 patients were responders to UPPP 4 to 8 years after treatment, and a low preoperative apnea hypopnea index (AHI) was a success factor. A 15‐year follow‐up of 50 OSAS patients after UPPP by our group showed a stable and significant decrease in oxygen desaturation index (ODI), and 65% of the patients had a postoperative ODI < 20 and a 50% reduction . The aim of the present study was to investigate the results from polysomnography after 6 and 24 months from all 65 operated patients in the SKUP 3 cohort, to evaluate whether their results were stable, and to determine whether there were any success factors that could help to refine the assessment concerning to which OSAS patients we should offer UPPP surgery.…”
Section: Introductionmentioning
confidence: 99%